Cattle Preference in Warm-Season Grasses: Effects of Seasonal Growth, Leaf Morphology, and Leaf Anatomy - Marcón, Florecia; Di Lorenzo, Elio Luis; Peichoto, Myriam Carolina; Acuña, Carlos Alberto (MDPI, 2025)
Warm-season grasses are the main source of feed in tropical and subtropical beef cattle production systems. The objective was to assess cattle preference among three warm-season grasses and explore its relationship with forage yield and plant structural traits. The three species were cultivated in 2 × 2 m plots using a completely randomized design. Cattle preference was evaluated in spring (December 2016 and 2017), summer (March 2017), and autumn (May2017) using six Braford steers that grazed the plots for 4 h on two consecutive days. Pre-grazing forage yield, plant height, leaf-blade length, leaf-blade width, and the proportions of five leaf tissues at three leaf regions were measured at each date. Cattle preference was variable among the three species and evaluation dates. Paspalum atratum exhibited the highest pre-grazing forage yield, and constituted the tallest plants with the longest leaves during the summer. Urochloa brizantha showed the greatest proportion of vascular bundle sheath (17–30% at the midrib region, 25–31% at the interveinal region and 14–23% at the margin region) and P. atratum exhibited the greatest number of primary vascular bundle. Cattle preference was negatively correlated with the number of primary vascular bundle, pre-grazing forage yield, plant height and leaf-blade length.